Implementation of space vector two-arm modulation for independent motor control drive fed by a five-leg inverter - Talib, Md Hairul Nizam; Ibrahim, Zulkifilie; Abd Rahim, Nasrudin; Abd Hasim, Ahmad Shukri (Korean Institute of Power Electronics (KIPE)., 2014)
This paper presents the implementation of two-arm modulation (TAM) technique for the independent control of a two-induction motor drive fed by a five-leg inverter (FLI). A carrier-based space vector pulse width modulation technique for TAM is proposed to generate switching signals for FLI. Two independent three-phase space vector modulators are utilized to control two motors. The motor drive system applies two separate indirect field-oriented control methods. The stationary voltage outputs from the vector control are synthesized in the three-phase space vector modulator to generate switching signals for FLI. The performance of the independent control of the motors and the voltage utilization factor are likewise analyzed. Simulation and experimental results verify the effectiveness of the proposed method for the independent control of the two-motor drive system. The proposed technique is successfully validated by dSPACE DS1103 experimental work.